2009
DOI: 10.1038/ja.2008.8
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of okilactomycin and congeners from Streptomyces scabrisporus by antisense differential sensitivity assay targeting ribosomal protein S4

Abstract: Protein synthesis inhibition is a highly successful target for developing clinically effective and safe antibiotics. There are several targets within the ribosomal machinery, and small ribosomal protein S4 (RPSD) is one of the newer targets. Screening of microbial extracts using antisense-sensitized rpsD Staphylococcus aureus strain led to isolation of okilactomycin and four new congeners from Streptomyces scabrisporus. The major compound, okilactomycin, was the most active, with a minimum detection concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…Researchers at Merck use eight different types of media for the cultivation of strains to make product library, from which new antimicrobial compounds such as platensimycin, platencin, philipimycin, fluvirucins, lucensimycins and okilactomycin have been isolated. [123][124][125][126][127][128] We used 10 different media (Table 1) for the cultivation of novel actinomycetes. [129][130][131] It was found that this was successful in obtaining a higher positive hit rate (70%) than the historical hit rate (1%) with the same screening methods (Table 2).…”
Section: Biodiversity Of Microbial Productsmentioning
confidence: 99%
“…Researchers at Merck use eight different types of media for the cultivation of strains to make product library, from which new antimicrobial compounds such as platensimycin, platencin, philipimycin, fluvirucins, lucensimycins and okilactomycin have been isolated. [123][124][125][126][127][128] We used 10 different media (Table 1) for the cultivation of novel actinomycetes. [129][130][131] It was found that this was successful in obtaining a higher positive hit rate (70%) than the historical hit rate (1%) with the same screening methods (Table 2).…”
Section: Biodiversity Of Microbial Productsmentioning
confidence: 99%
“…3 Second, we have expanded our efforts to isolate microorganisms from different geographical regions and habitats (including marine microbes) in combination with improved high-throughput fermentation methods. 4 The combination of these two approaches resulted in the discovery of a large number of natural products using either an rpsD-sensitized antisense strain [5][6][7][8][9][10] or fabH/fabF antisense-sensitized strains, including discovery of the FabF inhibitors platensimycin and platencin. [11][12][13][14][15][16][17] Recently, we have extended the antisense-based screening approach by constructing a S. aureus genome-wide fitness test assay and validated its use by mechanistically profiling a diverse set of 59 antibacterial compounds 18 and by the discovery of a new class of cell wall inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…14 Okilactomycin is a polyketide compound reported to have antitumor and weak antibacterial activity. 15 Recently, Zhang et al 16 confirmed that its mode of action in bacterial cells is via inhibition of RNA synthesis. Piloquinone is a phenanthrenequinone and exhibits antibacterial activity, 17 although the mode of action is not known.…”
mentioning
confidence: 97%